The role of chess in the development of children-parents’ perspectives - Nanu, Costica Ciprian; Coman, Claudiu; Bularca, Maria Cristina; Mesesan-Schmitz, Luiza; Gotea, Mihaela; Atudorei, Ioana; Turcu, Ioan; Negrila, Ion (Frontiers in Psychology, 2023)
The study examines the role of chess in the development of children from the perspectives of parents. The research focused on analyzing the parents' perceptions about chess's role in their children's development, on finding out how the perception of parents differs depending on whether they know how to play chess or not, and on outlining the profile of the parents whose children play chess.The study was conducted in Romania. In order to conduct the study, a quantitative research method was used, while having as a research instrument a non-standardized questionnaire. The questionnaire was applied to parents of chess-playing children who are members of chess clubs from Romania. The sample of the study comprises 774 respondents. The results of our research showed that parents are of the opinion that chess helps children develop their cognitive abilities, their character and their competitive spirit. Most of the parents focused on highlighting the positive effects of chess on the development of their children. Parents also considered that chess helped their children develop positive emotions and helped them overcome negative emotions. The results revealed differences between the opinions of parents depending on whether they know how to play chess or not. Thus, parents who do know how to play chess were more likely to focus on the positive effects of the game on the development of their children, and those who know how to play chess were also more satisfied with their children's accumulated knowledge following chess lessons. Findings extend our This is a provisional file, not the final typeset article understanding of how parents perceive the way chess influences the development of their children, it offered us a perspective on the perceived benefits of chess, benefits which should be further analyzed in order to identify under what circumstances chess could be introduced in the school curriculum.